RF front-end : world class designs - Love, Janine Sullivan; Ajluni, Cheryl J. (World class designs., 2009)
It all starts with a design ... this next book in the World Class Designs Series takes the best of our RF front end design material and creates a singular guide and catalyst for future projects!